2016
DOI: 10.1002/star.201600007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, composition, and physicochemical properties of starch from legumes: A review

Abstract: The review focuses on the structural, morphological, and physicochemical properties of starch from legume sources. The objective was to summarize some essential properties which are well documented in case of cereal and tuber starches as compared to legume starches. Starch is isolated using the dry or wet milling techniques. The amylose content of legume starches varies from normal to high in the range of 17.00-51.69%. Moisture content, lipid, ash, and nitrogen content of the legume starches have been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 102 publications
8
82
0
3
Order By: Relevance
“…Resistant starch in the corn starch was very low (0.12%), indicating higher susceptibility to enzymatic degradation by amylase compared to the bean starches (RS 5 30.52-60.28%). The amylose content in the bean starches ranged from 30.37 to 33.25%, which is within the range of amylose reported in bean starches (27-45%) (Du, Hongxin, Jay-Lin, & Yongfeng, 2014;Hoover & Ratnayake, 2002;Sandhu & Lim, 2008;Wani et al, 2016).…”
Section: Proximate Composition Of Starchessupporting
confidence: 80%
“…Resistant starch in the corn starch was very low (0.12%), indicating higher susceptibility to enzymatic degradation by amylase compared to the bean starches (RS 5 30.52-60.28%). The amylose content in the bean starches ranged from 30.37 to 33.25%, which is within the range of amylose reported in bean starches (27-45%) (Du, Hongxin, Jay-Lin, & Yongfeng, 2014;Hoover & Ratnayake, 2002;Sandhu & Lim, 2008;Wani et al, 2016).…”
Section: Proximate Composition Of Starchessupporting
confidence: 80%
“…Some starches appear in the form of agglomerates (G‐50 and wheat) while others tend to appear in the form of flakes (cassava and green bean). Such variation in morphology of starch granules, from different botanical sources, has been reported in several reviews and articles . It was also observed that the surface of starches extracted from either tuberous crop (potato, cassava, and sweet‐potato), vegetables (pea), or legumes (green bean) are smooth.…”
Section: Resultsmentioning
confidence: 68%
“…All the materials used in this experimental work are available commercially. Additionally, all the starches used in this work are popular food resources and the information related to their microstructures and molecular weights have been studied extensively …”
Section: Methodsmentioning
confidence: 99%
“…In particular, the high content of viscous soluble dietary fibre constituents, along with the relatively greater amylose (from 17% up to 52%) content when compared to starch from cereal grains, can mutually contribute to lowering the GI values of legumes, thus making legume flours and legume starches more suitable for promoting slow and moderate postprandial glucose and insulin responses in human subjects (Sandhu & Lim, 2008). In addition, legumes starches can form viscous pastes as compared to cereal starches, thus indicating high resistance to swelling and rupture (Wani et al, 2016). Detailed information concerning chemical composition and starch properties of several legume grains can be obtained elsewhere (Rebello et al, 2014;Wani et al, 2016).…”
Section: Gluten-free Foods: Legume Floursmentioning
confidence: 99%
“…In addition, legumes starches can form viscous pastes as compared to cereal starches, thus indicating high resistance to swelling and rupture (Wani et al, 2016). Detailed information concerning chemical composition and starch properties of several legume grains can be obtained elsewhere (Rebello et al, 2014;Wani et al, 2016).…”
Section: Gluten-free Foods: Legume Floursmentioning
confidence: 99%